The application of computational thinking and experiential learning concepts to improve algorithm skills among Junior High School Students of Salman Al Farisi Bandung - Erry Fuadillah (Privietlab, 2026)
Computational thinking (CT) is a 21st-century skill that is currently receiving widespread attention in many developed countries, where it has been incorporated into primary and secondary school curricula. Developing this skill requires a learning model that provides students with direct experience; one such model is experiential learning. This model emphasises that real-life experiences are the primary source of knowledge formation and computational thinking skills. This study aims to apply the concept of computational thinking to programming algorithms for junior high school students. This was achieved by comparing the learning outcomes of experimental classes that implemented an experiential learning model with computational thinking with those of a control class that used conventional methods. The results of the analysis showed that the average student learning outcome value in the experimental class was 87.826, compared to 81.36363 in the control class. Based on the t-test, the calculated t-value of 1.33676 is smaller than the t-table value of 1.68107, so H₀ is accepted and H₁ is rejected. Therefore, there is no significant difference in learning outcomes between the two groups. However, applying computational thinking through experiential learning models shows a positive upward trend in student learning outcomes and provides a more meaningful learning experience for understanding programming algorithm concepts.